2006
DOI: 10.1128/aem.00231-06
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of the nosZ Gene, Encoding Nitrous Oxide Reductase, and Comparison of the Abundances of 16S rRNA, narG , nirK , and nosZ Genes in Soils

Abstract: Nitrous oxide (N 2 O) is an important greenhouse gas in the troposphere controlling ozone concentration in the stratosphere through nitric oxide production. In order to quantify bacteria capable of N 2 O reduction, we developed a SYBR green quantitative real-time PCR assay targeting the nosZ gene encoding the catalytic subunit of the nitrous oxide reductase. Two independent sets of nosZ primers flanking the nosZ fragment previously used in diversity studies were designed and tested (K. Kloos, A. Mergel, C. Rös… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
409
5
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 863 publications
(472 citation statements)
references
References 32 publications
49
409
5
9
Order By: Relevance
“…For example, D. thunbergianus thalli are firmly attached to the soil (Fig. S1), which may produce local anaerobic conditions that promote processes involved in N 2 O production (Henry et al, 2006;Jones et al, 2013). The sharp increase and decrease of N 2 O fluxes and nitrate, respectively, in response to N amendment and under high rainfall frequency support this idea.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…For example, D. thunbergianus thalli are firmly attached to the soil (Fig. S1), which may produce local anaerobic conditions that promote processes involved in N 2 O production (Henry et al, 2006;Jones et al, 2013). The sharp increase and decrease of N 2 O fluxes and nitrate, respectively, in response to N amendment and under high rainfall frequency support this idea.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, nosZ gene is considered to be one of the most important functional genes associated with denitrification (Henry et al, 2006). Primer pairs of CrenamoA23f/CrenamoA616r (Tourna et al, 2008), amoA-1F/amoA-2R (Rotthauwe et al, 1997) and nosZ2F/nosZr (Henry et al, 2006) were used for quantifying amoA for AOA, AOB, and nosZ genes, respectively. Microbial species diversity (e.g.…”
Section: Quantification and Diversity Of Amoa And Nosz Genesmentioning
confidence: 99%
“…But Chronakova et al (2009) found the nosZ gene copy number was in a range of 9.1×10 7 -7.5×10 9 copies g −1 soil in an upland pasture soil. Henry et al (2006) found there was no significant difference between the abundances of nosZ and nirK in an agricultural soil of France. Thus, the abundances of soil nirS, nirK, and nosZ genes might be closely related to the properties of soil samples, especially when the management practices were different.…”
Section: Abundances Of Nirs Nirk and Nosz Genes Under Different Irrmentioning
confidence: 66%
“…The samples were then homogenized for 3 Â 30 s at 4 m s À 1 in a FastPrep-24 (MP-Biomedicals, Santa Ana, CA, USA) and incubated for 30 min at 70 1C before centrifugation at 7.000 Â g for 5 min at 20 1C. Quantification of the denitrifier community abundance Evaluation of the denitrifier abundances by quantitative PCR was performed for all sampling times according to Henry et al (2006) using the nosZ gene as a molecular marker as previously performed (Scala and Kerkhof, 1999;Horn et al, 2006;Kjellin et al, 2007 Barcoded pyrosequencing analyses of the denitrifier community The denitrifier community composition was assessed just before the addition of wheat shoot residues, that is, 6 weeks after inoculation to enable the soil colonization by the inoculated microorganisms. DNA extracts from the triplicate microcosms inoculated with the different dilutions were amplified using a two-step PCR procedure as recommended by Berry et al ( 2012) for barcoded pyrosequencing.…”
Section: Dna Extractionmentioning
confidence: 99%